2020
DOI: 10.1002/dmrr.3275
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of offloading interventions to heal foot ulcers in persons with diabetes: a systematic review

Abstract: Background Offloading interventions are commonly used in clinical practice to heal foot ulcers. The aim of this updated systematic review is to investigate the effectiveness of offloading interventions to heal diabetic foot ulcers. Methods We updated our previous systematic review search of PubMed, EMBASE, and Cochrane databases to also include original studies published between July 29, 2014 and August 13, 2018 relating to four offloading intervention categories in populations with diabetic foot ulcers: (a) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
260
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 92 publications
(263 citation statements)
references
References 149 publications
(904 reference statements)
2
260
0
1
Order By: Relevance
“…66 A removable knee-high device also redistributes pressure more effectively than a removable ankle-high offloading device (such as anklehigh walker, forefoot offloading shoes, half shoes, cast shoes, or postoperative sandal). 6,10,19,33 Our systematic review 31 identified one high-quality metaanalysis, 34 that included two low-quality RCTs, 38,43 and found no difference in the proportion of plantar forefoot ulcers healed between removable knee-and ankle-high offloading devices (healing sandal or half shoe) (P = 0.20). 34 A more recent high-quality RCT also found no difference in plantar forefoot ulcers healed between a removable knee-high device (bivalved TCC) and either a removable ankle-high cast shoe or forefoot offloading shoe, at either 12 weeks (P = 0.703) or 20 weeks (P = 0.305).…”
Section: Rationalementioning
confidence: 94%
See 3 more Smart Citations
“…66 A removable knee-high device also redistributes pressure more effectively than a removable ankle-high offloading device (such as anklehigh walker, forefoot offloading shoes, half shoes, cast shoes, or postoperative sandal). 6,10,19,33 Our systematic review 31 identified one high-quality metaanalysis, 34 that included two low-quality RCTs, 38,43 and found no difference in the proportion of plantar forefoot ulcers healed between removable knee-and ankle-high offloading devices (healing sandal or half shoe) (P = 0.20). 34 A more recent high-quality RCT also found no difference in plantar forefoot ulcers healed between a removable knee-high device (bivalved TCC) and either a removable ankle-high cast shoe or forefoot offloading shoe, at either 12 weeks (P = 0.703) or 20 weeks (P = 0.305).…”
Section: Rationalementioning
confidence: 94%
“…• Added a new recommendation on offloading treatments for people with neuropathic plantar heel ulcers. Our updated systematic review 31 identified five high-quality meta-analyses of controlled trials on this topic, [33][34][35][36][37] with much overlap present between the meta-analyses on the trials included. All found that nonremovable offloading devices result in significantly improved healing outcomes for neuropathic plantar forefoot ulcers when compared with removable devices (removable offloading devices or footwear).…”
Section: What's New?mentioning
confidence: 99%
See 2 more Smart Citations
“…International guidelines recommend the use of custom-made footwear to help prevent diabetic foot ulceration, with target pressures for footwear provided for those patients who healed from a plantar foot ulcer. [1][2][3][4][5] While the goals for custom-made footwear are clear and clinical decision-making in selecting the type of footwear is often defined by the degree of foot deformity present, footwear design can be variable and is hardly supported by any published protocol, shoe concept or algorithm. Only two consensus-based algorithms for custom-made footwear and a pressure-and foot shape-guided design algorithm for custom-made insoles have been identified in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%